2015
DOI: 10.1002/ejoc.201501077
|View full text |Cite
|
Sign up to set email alerts
|

Functional Molecules for Grafting onto Ionic Surfaces

Abstract: The 2D adsorption of molecules onto insulating surfaces is of increasing interest for future devices in emerging technologies such as molecular electronics, sensors, single‐molecule optics, and on‐surface synthesis. However, most attempts to stabilize molecular structures on these substrates have been hampered by weak molecule–surface interactions and so there is a need to develop organic molecules bearing suitable grafting groups. We report herein the synthesis of a series of molecules designed to be physisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Use of amino acids provides an inexpensive approach to introduce chirality into the side chains. Although Stoddart et al reported sugar appended triphenylenes capable of forming lyotropic mesophases with organic solvents back in 2001 16 , and others have reported organogelating triphenylenes containing amide groups 17,19,20,21,24 , the only previous reports of triphenylene amino acid conjugates of which we are aware are three compounds reported by Bechgaard et al in 1997 33 but not investigated for lyotropic behaviour (the tert butyl, rather than ethyl, derivatives of $ and $ , and the deprotected carboxylic acid variant of $ ), and a recently reported triphenylene homoserine conjugate whose self assembly properties have not yet been reported 34 . Only two examples have been reported of triphenylene organogelators with chiral side chains 16,20 .…”
Section: ! "mentioning
confidence: 84%
“…Use of amino acids provides an inexpensive approach to introduce chirality into the side chains. Although Stoddart et al reported sugar appended triphenylenes capable of forming lyotropic mesophases with organic solvents back in 2001 16 , and others have reported organogelating triphenylenes containing amide groups 17,19,20,21,24 , the only previous reports of triphenylene amino acid conjugates of which we are aware are three compounds reported by Bechgaard et al in 1997 33 but not investigated for lyotropic behaviour (the tert butyl, rather than ethyl, derivatives of $ and $ , and the deprotected carboxylic acid variant of $ ), and a recently reported triphenylene homoserine conjugate whose self assembly properties have not yet been reported 34 . Only two examples have been reported of triphenylene organogelators with chiral side chains 16,20 .…”
Section: ! "mentioning
confidence: 84%
“…37 The previously reported method for the preparation of derivative 38 involves multiple steps, requires longer reaction time, and furnishes the product in moderate yield. 38 The isatin (1H-indole-2,3-dione) moiety is a privileged scaffold for chemical modification and is responsible for a broad spectrum of biological properties in many synthetically versatile molecules. 39 Similarly, coumarin derivatives are plant-derived natural products known for their diverse pharmacological properties.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%